Antimicrobial Susceptibility Patterns of Klebsiella Species Causing Urinary Tract Infections in Pregnant Women - Haque, Quazi Tamanna; Alam, Md Shah; Sazzad, Jarin; Ali, Md Tamjid; Haque, Md Ahsanul; Rahman, Md Mizanur; Nadi, Sumona Raisa (TAJ: Journal of Teachers Association, 2023)
Background: Urinary tract infections (UTIs) are the most prevalent type of infection during pregnancy and are notoriously difficult to treat. Significant maternal and fetal risk is associated with UTI during pregnancy, with the most prevalent clinical manifestations being asymptomatic bacteriuria, acute cystitis, and acute pyelonephritis. Objectives: To identify Klebsiella species causing urinary tract infection among pregnant women and its antimicrobial susceptibility pattern by modified Kirby Bauer disc diffusion method in Rajshahi Medical College Hospital. Materials and Method: A descriptive cross-sectional study was conducted between July 2021 to June 2022 in the Microbiology Department of Rajshahi medical college and the Gynecology and Obstetrics Department of RMCH to determine the antimicrobial susceptibility pattern of Klebsiella species causing urinary tract infection in pregnant women. The urine samples were inoculated onto MacConkeys agar, blood agar, nutrient agar, and chromogenic UTI agar media and incubated aerobically at 370 C overnight (18-20 hrs). Results: In all trimesters, 294 urine samples were obtained from pregnant women with asymptomatic and symptomatic UTIs. Among the 114 (38.77%) culture-positive samples, 111 (97.36%) were single isolates, whereas 3 (2.63%) included multiple isolates. Klebsiella spp. comprised 21 out of 117 culture-positive bacterial isolates (17.94%). Regarding antimicrobial susceptibility testing, Klebsiella spp. demonstrated a significant degree of sensitivity to meropenem and nitrofurantoin. In this investigation, Klebsiella spp. was found to be the cause of bacteriuria among pregnant women. Conclusion: Doctors should adhere to the antimicrobial susceptibility test results when selecting the appropriate medications to treat pregnant women with UTIs. TAJ 2022; 36: No-1: 41-46